Concepção de transformação linear por estudantes de licenciatura em matemática - Silva, Maria Eliana Santana da Cruz (2016)
This doctoral dissertation reports an investigation of the conceptions of linear transformation held by teaching certification students in mathematics following a course of linear algebra devised to involve students in the search for elements to build the concept of this mathematical object. The analysis of these conceptions was carried out according to the APOS theory by Dubinsky and Lewin (1986) and Asiala et al. (1996), in articulation with premises of didactic engineering (MACHADO, 2010). The investigation was a qualitative, case-study type, which, according to Bogdan and Biklen (1994) and Lüdke and André (1986), enables the context studied to be investigated and interpreted, given that all qualitative studies seek to portray reality in a more dense fashion and represent the different perspectives present in a given social situation. Centered on this understanding of qualitative research, classes were organized with the aim of actively involving the study participants to facilitate data collection, which was carried out three semesters after the linear algebra course. Premises of didactic engineering were employed to prepare and conduct the activities, which were discussed and solved by paired students. Their interactions were audio recorded and also noted by an observer. The analysis revealed that the subjects paired for the activities experienced different stages in terms of conception (action, process, and object) in most of the activities. We concluded that the students investigated did not always show a conception of object during the activities, but were all able to demonstrate a conception of process for the notion of linear transformation